Novel composite phase change material of high heat storage and photothermal conversion ability. (May 2022) - Zhou, Bo; Zhen, Liping; Yang, Yongjie; Ma, Wenli; Fu, Yilin; Duan, Xiaoya; Wang, Huazhi
Highlights: Mesoporous silica coated carbon nanotubes (CNTs@MS) with core-shell structure was prepared. The melting latent heat of SA/CNTs@MS composites was up to 125.6 J/g. The composite phase change material (PCM) exhibited excellent shape stability and thermal reliability. Photo-thermal conversion property and thermal conductivity were significantly improved by introducing CNTs. Abstract: Using porous matrix as the supports for phase change materials (PCMs) can effectively eliminate the leakage problem of PCMs during the phase change process. In heat storage utilization, the as-prepared shape-stabilized phase change materials are highly desired to have high latent heat density, rapid heat transfer ability and less supercooling. Although mesoporous silica with large pore volume and specific surface area might be a promising matrix for PCMs, it would be more beneficial if its thermal conductivity and photo-thermal conversion capacity were further improved, especially for the utilization of solar thermal energy. Herein, a composite PCM, namely SA/CNTs@MS, was fabricated successfully using mesoporous silica coated carbon nanotubes (CNTs@MS) as the shape-stabilized matrix for the PCM stearic acid (SA). The results of characterizations showed that CNTs@MS had a core-shell structure with mesoporous silica of a thickness of about 30 nm coated on the outer surface of carbon tubes (CNTs) homogeneously. The melting enthalpy of the obtained SA/CNTs@MS composite was 125.6 J/g. Its thermal conductivity increased 64.7%, and the supercooling degree decreased 3.2 ℃ while compared with those of pure SA. The melting and solidification enthalpies of SA/CNTs@MS decreased 1.1% and 1.3%, respectively after 200 thermal cycles. Besides, it is also confirmed that SA/CNTs@MS had good photo-thermal conversion performance. These imply that the synthesized SA/CNTs@MS composite would be an ideal heat storage material, especially for solar energy utilization.